A Comparison of Phenolic Monomers Produced from Different Types of Lignin by Phosphotungstic Acid Catalysts. Issue 5 (23rd May 2019) - Du, Boyu; Liu, Bingyang; Wang, Xing; Zhou, Jinghui
Abstract: Herein we studied the chemical structure of different types of lignin samples and the potential to prepare phenolic monomers was illustrated by phosphotungstic acid catalysts. Different types of H/G/S lignin components had different structures. The lignin extracted from poplar had the highest molecular weight and β‐O‐4 aryl ether contents, followed by pine and straw lignin samples. After depolymerization by PTA catalyst, the yields of phenolic monomers detected was 8.06 wt % (poplar), 5.44 wt % (pine) and 4.52 wt % (straw), respectively. Further, the ratios of H/G/S in the phenol monomers were also different, indicating that the S, G and H types structural units were continuously transformed with each other during the reaction. In our study, the change in the types of lignin samples resulted into an improvement of the distribution of phenolic products, and also the selectivity of phenolic monomers significantly. Abstract : Lignin explained : Phosphotungstic acid polyoxometalate catalyst showed high activity in the selective depolymerization of three types of lignin samples to phenolic monomers, and the impact of the structure differences on the distribution of phenolic monomers were well studied. Emphasis was placed on changing the types of lignin samples to control the secondary depolymerization of methoxy groups and greatly improving the selectivity of phenolic monomers.